miR-874 regulates myocardial necrosis by targeting caspase-8 - Wang, K (Nature Publishing Group, 2013)
Cardiomyocyte death is an important reason for the cardiac syndromes, such as heart failure (HF) and myocardial infarction (MI). In the heart diseases, necrosis is one of the main forms of cell death. MicroRNAs (miRNAs) are a class of small non-coding RNAs that mediate post-transcriptional gene silencing. Hitherto, it is not yet clear whether miRNA can regulate necrosis in cardiomyocyte. In this work, we performed a microarray to detect miRNAs in response to H2O2 treatment, and the results showed that miR-874 was substantially increased. We further studied the function of miR-874, and observed that knockdown of miR-874 attenuated necrosis in the cellular model and also MI in the animal model. We searched for the downstream mediator of miR-874 and identified that caspase-8 was a target of miR-874. Caspase-8 was able to antagonize necrosis. When suppressed by miR-874, caspase-8 lost the ability to repress necrotic program. In exploring the molecular mechanism by which miR-874 expression is regulated, we identified that Foxo3a could transcriptionally repress miR-874 expression. Foxo3a transgenic or knockout mice exhibited a low or high expression level of miR-874, and a reduced or enhanced necrosis and MI. Our present study reveals a novel myocardial necrotic regulating model, which is composed of Foxo3a, miR-874 and caspase-8. Modulation of their levels may provide a new approach for tackling myocardial necrosis.